Technical Analysis of NVIDIA Stock - Akkabak, Azat; Janda, Karel; Folprecht, Marek; Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví (2025)
The thesis aims to explain NVIDIA (NVDA) price behavior and translate it into practical rules for short‑, medium‑, and long‑term horizons. The study uses price and volume data for 2020–2025 (TradingView) and a small set of common chart tools (moving averages, oscillators, volatility bands) across four timeframes (weekly, daily, 4h, 1h). The output is a set of clear rules for when to enter, when to exit, and when to abandon a scenario. The main contribution is a simple, repeatable workflow, making the guidance accessible to readers who may not be proficient users of specialized technical analysis software. The conclusions provide a concise synthesis of these practical rules together with risk‑control guidelines. This work is intended for academic purposes and does not constitute investment advice.
Vedoucí práce: Karel Janda
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: bankovnictví a pojišťovnictví [obor bakal. práce]; bakalářské práce; bachelor's theses